Peran Kegiatan Fun cooking dan Country Project dalam Kemampuan Matematika Awal dan Berpikir Kritis Anak Usia Dini - Rini Herminastiti (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2019)
AbstractThis study aims to determine the role of fun cooking and country project in developing the ability of early mathematics and critical thinking of early childhood in PAUD AL-Fitri Jakarta. The subjects of this study were children aged 5-6 years in Group B which consist 10 children. The method used is a descriptive qualitative approach with data collection techniques using observation, interviews, and documentation. The data is then processed through Engineering triangulation. Based on the results of the child's research, information was obtained that the activities of fun cooking and country projects that were integrated according to the theme had a role in the children ability of early Mathematics and critical thinking. Fun cooking and Country Project activities have a role in the ability of early Mathematics of children, especially in grouping, counting, calculating and weighing the amount of food that need to be processed or supporting activities. Fun cooking and Country Project activities have a role in children's critical thinking ability when children classify and connect the prepared food to certain regions in Indonesia or the world. In addition, when making these foods, children use their critical thinking skills when taking steps to cook in sequence, associating the amount of food with numerical symbols and the distinctiveness of taste, and the smell of food made. Keywords: fun cooking, country project, early Mathematics ability, critical thinking ability.   AbstrakPenelitian ini bertujuan untuk mengetahui peran fun coooking dan country project dalam mengembangkan kemampuan Matematika awal dan berpikir kritis anak usia dini di PAUD AL-Fitri Jakarta. Subjek penelitian ini adalah anak usia 5-6 tahun, Kelompok B berjumlah 10 orang. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Data selanjutnya diproses melalui triangulasi Teknik. Berdasarkan hasil penelitian anak, diperoleh informasi bahwa kegiatan fun cooking dan country project yang terintegrasi sesuai tema memiliki peran dalam kemampuan Matematika awal dan berpikir kritis anak. Kegiatan fun cooking dan Country Project memiliki peran dalam kemampuan Matematika awal anak terutama dalam mengelompokan, membilang, menghitung dan menimbang jumlah bahan makanan yang akan diolah ataupun kegiatan pendukung. Kegiatan fun cooking dan Country Project memiliki peran dalam kemampuan berpikir kritis anak ketika anak mengklasifikasikan dan menghubungkan makanan yang akan disiapkan merupakan makanan khas daerah tertentu di Indonesia atau dunia. Selain itu ketika membuat makanan tersebut anak menggunakan kemampuan berpikir kritisnya ketika melakukan langkah-langkah memasak secara berurutan, mengaitkan jumlah bahan makanan dengan simbol-simbol angka maupun kekhasan rasa, aroma dari makanan yang dibuat.   Kata Kunci:  fun cooking, country project, kemampuan matematika awal, kemampuan berpikir kritis